A Functional Dissection of the mRNA and Locally Synthesized Protein Population in Neuronal Dendrites and Axons - Perez, Julio D.; Fusco, Claudia M.; Schuman, Erin M. (Annual Review of Genetics, 2021)
Neurons are characterized by a complex morphology that enables the generation of subcellular compartments with unique biochemical and biophysical properties, such as dendrites, axons, and synapses. To sustain these different compartments and carry a wide array of elaborate operations, neurons express a diverse repertoire of gene products. Extensive regulation at both the messenger RNA (mRNA) and protein levels allows for the differentiation of subcellular compartments as well as numerous forms of plasticity in response to variable stimuli. Among the multiple mechanisms that control cellular functions, mRNA translation is manipulated by neurons to regulate where and when a protein emerges. Interestingly, transcriptomic and translatomic profiles of both dendrites and axons have revealed that the mRNA population only partially predicts the local protein population and that this relation significantly varies between different gene groups. Here, we describe the space that local translation occupies within the large molecular and regulatory complexity of neurons, in contrast to other modes of regulation. We then discuss the specialized organization of mRNAs within different neuronal compartments, as revealed by profiles of the local transcriptome. Finally, we discuss the features and functional implications of both locally correlated—and anticorrelated—mRNA-protein relations both under baseline conditions and during synaptic plasticity.
Keywords: synaptic plasticity